Keanekaragaman Jenis Rangkong dan Tumbuhan Pakannya di Harapan Rainforest Jambi (Species and Feed Diversity of Hornbill in the Harapan Rainforest, Jambi) - Very ANGGRIAWAN; Bambang HARIYADI; Muswita MUSWITA (Universitas Jambi, 2015)
Hornbill has an important role in forest regeneration, but the limited variety andamount of food available to birds will eventually threaten the population of hornbills.Identification of feed plant and hornbil species diversity was conducted at the HarapanRainforest from March to April 2011. Hornbills plant feed samples were taken right after thebirds were eating. The results showed there are nine plant species of hornbills feed found in theHarapan Rainforest: Santiria apiculata, Elaeocarpus sphaericus, Sapium baccatum, Lithocarpusreinwardtii, Disoxylum excelsum, Ficus curtipes, Knema globularia, Knema furfuracea, andSantiria oblongifolia. Of these nine species, Ficus curtipes is the most preferred feed by thehornbills. Further research also notes that there are seven hornbill species inhabit the HarapanRainforest: crested hornbills (Aceros comatus), rhinoceros hornbills (Buceros rhinoceros), goldhornbill (Aceros undulatus), black kangkareng (Anthracaceros malayanus), black-crestedhornbill (Aceros corrugatus), khilingan hornbills (Anorrhinus galeritus) and ivory hornbill(Rhinoplax vigil)